Patenting Stem Cell Technologies in Europe - Sheard, Andrew (Cold Spring Harb Perspect Med, 2015)
European patent law as it applies to stem cell technologies is complex. The complexities have developed from different supranational sources of law during the last 50 years and from the various levels of exceptions to patentability embodied in the law. In relation to stem cells of human embryonic origin, the definition of a human embryo, although broad, is still in some respects unclear; and the definition of what constitutes the use of a human embryo for industrial or commercial purposes, which is excluded from patentability in Europe, is also remarkably broad. Further clarification is awaited from the courts and from the Boards of Appeal of the European Patent Office.